Bariatric diagnostic CT scanning: A radiotherapy perspective. Issue 3 (August 2015) - Smith, S.; St John-Matthews, J.; Fox, L.; Weaving, V.
Abstract Obesity is increasing in the United Kingdom. Equipment available for this patient group including wheelchairs, beds and hoists is becoming more common in the hospital environment; diagnostic imaging equipment that can accommodate bariatric patients has not increased at the same rate. Subsequently these service-users are often unable to receive "gold-standard" cross-sectional imaging within their patient-pathway. This paper highlights how a diagnostic imaging department has utilised wide-bore CT scanning equipment within the radiotherapy setting to ensure an equitable service for all service users. Through literature review and local experience, a standard operating procedure and scanning service has been developed. Areas explored include technical consideration of scanner design; patient positioning; image artefacts and intravenous contrast administration. Also investigated is patient wellbeing incorporating manual handling, respiration and psycho-social needs. Additionally, demonstration of how interprofessional collaboration by diagnostic and radiotherapy radiographers can ensure the best imaging experience and outcome for this patient group.